2013
DOI: 10.1177/159101991301900405
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Reproduction of Device Deformation Leading to Thrombotic Complications and Failure of Flow Diversion

Abstract: Flow diverters (FDs) are increasingly used for complex intracranial aneurysms. As these self-expanding devices are deployed across an aneurysm neck, they can undergo deformations. The potential clinical consequences of FD deformations remain unclear. We describe an immediate thrombotic complication attributed to a stereotypical stenotic deformation of an FD extremity that can occur when landing zones are of insufficient length. This case is supplemented with in vitro studies showing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 13 publications
0
29
0
Order By: Relevance
“…Several mechanisms underlying FDD recurrence or failure have been put forward: endoleak of the aneurysm sac11; FDD deformation leading to increased pore size and persistent blood entry into the aneurysm12; FDD deformation caused by inappropriate device diameter and length of the landing zone leading to deformation related complications; and failure of FDDs, which was proved by in vitro research 13…”
Section: Discussionmentioning
confidence: 99%
“…Several mechanisms underlying FDD recurrence or failure have been put forward: endoleak of the aneurysm sac11; FDD deformation leading to increased pore size and persistent blood entry into the aneurysm12; FDD deformation caused by inappropriate device diameter and length of the landing zone leading to deformation related complications; and failure of FDDs, which was proved by in vitro research 13…”
Section: Discussionmentioning
confidence: 99%
“…In addition, they observed a transition zone of variable porosity at the neck level associated with an inhomogeneous endothelial tissue colonization of the device scaffold, which could be associated with a treatment failure. Besides, Estrade et al 37 reported a case with very bad delayed outcomes related to implantation issues: A too-short landing zone and an oversized device induced a proximal conically deformed stent and a stenosis followed by immediate thromboembolic complications.…”
Section: Discussionmentioning
confidence: 99%
“…In this transitional zone, metal coverage is lower, porosity is higher and on follow-up neointima formation is poor (14,16). In other words, as there is a direct relation between lower porosity of the 'free segment of the stent' (FSS) facing the aneurysm cavity and success of aneurysm occlusion (6,7), the increased porosity at TZ will result in sustained leak into the aneurysm and increase the risk of residual aneurysms after flow diversion (2,9,13,15,16). Focal zones of low porosity and residual flow specifically occur in curved segments or wide-neck aneurysms due to the deformation of the FD (8,13).…”
Section: █ Discussionmentioning
confidence: 99%
“…The discrepancy between the size of the landing zones will result in undersizing or oversizing of the device at either the proximal landing zone or the distal one based on what the operator chooses as his/her reference for the sizing of the flow diverter (16). Inevitably, there will be a conical transitional zone (TZ) between the fully expanded or even over expanded segment crossing the aneurysm and the relatively constrained distal or proximal landing zones (9). In this transitional zone, metal coverage is lower, porosity is higher and on follow-up neointima formation is poor (14,16).…”
Section: █ Discussionmentioning
confidence: 99%